Thursday

August 28, 2014

August 28, 2014

Posted by **Taylor** on Friday, October 12, 2012 at 1:47am.

f(x)=Squareroot 4-x; g(x)=1-3x^2

Find (gof)(-2) for the same problem.

- Math -
**Reiny**, Friday, October 12, 2012 at 8:57am(fog)2 = f(f(2))

g(2) = 1 - 12 = -11

f(g(2) = f(-11) = √(4 -(-11)) = √15

do the second one in the same way

**Related Questions**

college algebra - 1. answer the following for the given quadratic function f(x)=...

Composite Functions - f(x)=(7x+28)/(x-3) and g(x)=(3x+28)/(x-7) Find: (fog)(x) (...

math - Find (gof)(-2) f(x)=Squareroot of 4-x; g(x)=1-3x^2

Algebra - If f(x)= ln x, g(x) = e^3x, and h(x) = x^7, find the following... a) (...

math - Find a. fog b. gof c. fof d. gog f(x)=4-x g(x)=3x-5

math - Find a. fog b. gof c. fof d. gog for each function f(x)=4-x g(x)=3x-5

Math - Find (fog)(2) and (gof)(-2) f(x)=Square root of 4-x; g(x)=1-3x^2 Show ...

Algebra help - Find (fog)(x)and (gof)(x)if f(x)=x-x^2 and g(x)= 2x+3.

Algebra 2 - If f(x) = x-3 g(x) = 2x+5 find fog and gof

Algebra help - Find (fog)(x)and (gof)(x)if f(x)=x-x^2 and g(x)= 2x+3. Okay so I ...